Qualidade e honorários de auditoria: um estudo das companhias listadas na BM&FBOVESPA - Moreira, Felipe da Silva (Brasil, 2017)
The present study aims to present an analysis of the influence of the quality of the audit from the results management, about the fees charged by independent auditors in Brazil. During the last decade, the work on the audit fees gained relevance in the Brazilian scenario from the disclosure of the amounts paid to independent auditors, given that the requirement for such information gave only from 2009 through the CVM Instruction 480/2009 of the Comissão de Valores Mobiliários. In this context, the discussion on the audit fees intensifies when the market share of the Big Four companies. Otherwise, it also discusses the quality of the services provided by the big firms, especially in events of financial fraud or improper procedures audit companies, as for example, issuance of opinion without the submission of working papers, which may reveal a flawed criterion of studies to determine the quality of auditing only due to be a Big Four. From the reality found, this research seeks to contribute to an analysis of the cost-benefit of services, monitoring the pricing policies of the auditing firms, in addition to enabling audit firms also to check the amount of fees collected as a function of the quality of service being provided, assisting them in negotiations and maintaining customers. To achieve this goal, the research uses data from Brazilian non-financial companies listed on the BM&FBovespa during the period from 2010 to 2015. Data collection occurred through the Bloomberg® and Reference Forms after tab, are submitted in regression models with panel data. The main analysis variables comprise the audit fees (dependent variable) and audit quality (variable of interest), this obtained through the model KS (1995) earnings management for discretionary accruals. The main results show that cannot infer statistical relationship between audit fees and the audit quality, however demonstrate that an analysis of the size and risk of the audited company are positively related with the fees, as well as the fact that the company be a Big Four.
Keywords: Honorários de auditoria; Qualidade de auditoria; Gerenciamento de resultados; CNPQ::CIENCIAS SOCIAIS APLICADAS: CIÊNCIAS CONTÁBEIS